Cardiac Troponin T Response during High-Intensity Competition and its Correlation with the Corrected QT Interval among the Trained Athletes - Alireza Kashef; Fereshteh Shahidi; Alireza Sadeghi Nikoo (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2020)
Introduction: It is highly crucial to develop novel strategies in order to further enhance the monitoring of sudden cardiac arrest in athletes and establish standard medical care procedures to control monitoring and treatment costs. Therefore, this study aimed to investigate the effects of a high-intensity competition on cardiac troponin T (cTnT) and its correlation with the corrected QT interval (QTc) in the trained athletes.